An Induced Pluripotent Stem Cell Model of Hypoplastic Left Heart Syndrome (HLHS) Reveals Multiple Expression and Functional Differences in HLHS‐Derived Cardiac Myocytes. (3rd March 2014) - Jiang, Yan; Habibollah, Saba; Tilgner, Katarzyna; Collin, Joseph; Barta, Tomas; Al-Aama, Jumana Yousuf; Tesarov, Lenka; Hussain, Rafiqul; Trafford, Andrew W.; Kirkwood, Graham; Sernagor, Evelyne; Eleftheriou, Cyril G.; et al.
Abstract : This study generated an induced pluripotent stem cell (iPSC) model of hypoplastic left heart syndrome (HLHS) malformation and characterized the properties of cardiac myocytes (CMs) differentiated from these and control‐iPSC lines. CMs derived from an HLHS patient demonstrate a number of marker expression and functional differences to human embryonic stem cells/control iPSC‐derived CMs, thus providing some evidence that cardiomyocyte‐specific factors may influence the risk of HLHS. Abstract : Hypoplastic left heart syndrome (HLHS) is a serious congenital cardiovascular malformation resulting in hypoplasia or atresia of the left ventricle, ascending aorta, and aortic and mitral valves. Diminished flow through the left side of the heart is clearly a key contributor to the condition, but any myocardial susceptibility component is as yet undefined. Using recent advances in the field of induced pluripotent stem cells (iPSCs), we have been able to generate an iPSC model of HLHS malformation and characterize the properties of cardiac myocytes (CMs) differentiated from these and control‐iPSC lines. Differentiation of HLHS‐iPSCs to cardiac lineages revealed changes in the expression of key cardiac markers and a lower ability to give rise to beating clusters when compared with control‐iPSCs and human embryonic stem cells (hESCs). HLHS‐iPSC‐derived CMs show a lower level of myofibrillar organization, persistence of a fetal gene expression pattern, and changes in commitment to ventricular versus atrial lineages, and they display different calcium transient patterns and electrophysiological responses to caffeine and β‐adrenergic antagonists when compared with hESC‐ and control‐iPSC‐derived CMs, suggesting that alternative mechanisms to release calcium from intracellular stores such as the inositol trisphosphate receptor may exist in HLHS in addition to the ryanodine receptor thought to function in control‐iPSC‐derived CMs. Together our findings demonstrate that CMs derived from an HLHS patient demonstrate a number of marker expression and functional differences to hESC/control iPSC‐derived CMs, thus providing some evidence that cardiomyocyte‐specific factors may influence the risk of HLHS.